2021
DOI: 10.1159/000515273
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disease Is Associated with Higher Age-Related Macular Degeneration Risk: Results from a Meta-Analysis of Epidemiologic Studies

Abstract: Background: Although epidemiologic studies have suggested that thyroid disease may be a risk factor for age-related macular degeneration (AMD), this finding is still controversial. Objectives: The aim of this meta-analysis was to investigate whether an association exists between thyroid disease and medication and AMD in epidemiologic studies. Methods: We searched PubMed, EMBASE, and Google Scholar from their inception to March 2020 for cross-sectional, case-control and cohort studies that assessed thyroid func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A Taiwan population-based study indicated that insomnia is an independent indicator of an increased risk of AMD ( Tsai et al, 2020 ). Thyroid disease is associated with an increased risk of AMD ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Taiwan population-based study indicated that insomnia is an independent indicator of an increased risk of AMD ( Tsai et al, 2020 ). Thyroid disease is associated with an increased risk of AMD ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(3) TH signaling has been associated with human cone/retinal diseases. Population-based/patient-based studies have shown strong evidence for the association between elevated TH level in the circulation/hyperthyroidism and increased incidence of AMD (atrophic/dry AMD; Age-Related Eye Disease Study Research Group, 2000 ; Chaker et al, 2015 ; Gopinath et al, 2016 ; Chatziralli et al, 2017 ; Lin et al, 2018 ; Abdelkader and Abass, 2019 ; Farvardin et al, 2021 ; Xu et al, 2021 ; Hung et al, 2022 ; Li et al, 2022 ). Optical coherence tomography evaluation shows macular thinning in patients with thyroid-associated ophthalmopathy ( Sayın et al, 2016 ; Blum Meirovitch et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive TH signaling has been shown to induce auditory defects/cochlear degeneration ( Ng et al, 2009b ) and cerebellum degeneration ( Peeters et al, 2013 ) in mice. More importantly, TH signaling has been linked to neurodegenerative conditions in humans, including Alzheimer’s disease ( Kalmijn et al, 2000 ; Ceresini et al, 2009 ) and age-related macular degeneration (AMD; Age-Related Eye Disease Study Research Group, 2000 ; Chaker et al, 2015 ; Gopinath et al, 2016 ; Chatziralli et al, 2017 ; Lin et al, 2018 ; Abdelkader and Abass, 2019 ; Farvardin et al, 2021 ; Xu et al, 2021 ; Hung et al, 2022 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no statistical association was reported between thyroid medication and AMD risk, although they could not conduct subgroup analyses according to AMD type. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Some recently performed studies have proposed that thyroid dysfunction may also be considered a modifiable risk factor for AMD. 9 10 11 12 In fact, thyroid dysfunction predisposes the individual to other risk factors such as dyslipidemia, atherosclerosis, and hypertension. Moreover, recent investigations in this regard have reported that the suppression of thyroid hormone signaling was associated with cone photoreceptors preservation in mouse models.…”
Section: Introductionmentioning
confidence: 99%